Estética em revolução - Domingos, Adenil Alfeu [UNESP]; Cortez, Clarice Zamonaro; Serrano, Eliane Patrícia Grandini [UNESP]; Biondo, Guiomar Josefina [UNESP]; Costa, Maria Luiza Calim de Carvalho [UNESP]; Salzedas, Nelyse Apparecida Melro [UNESP]; Brito, Sônia de [UNESP] (My University, 2012)
The difficulty lies in dealing with the texts of Almada Negreiros focuses on language, search for expression. Saramago, in his texts of various kinds, "Manual of Painting and Calligraphy" and "The world's largest flower," suffers by seeking representative languages. Which one is less difficult, less traumatic, painting or writing? In conclusion, the two are so much paint as painful to write. Compare them to the knife ripping a sheet of paper. Almada entangled in them all as a poet, novelist, painter, designer, playwright. Through them, we sought from "Before You Begin" to "Getting Started", always be in alpha. The text that follows is entitled Aesthetics in Revolution, it may cover the surrounding poetic Alma.
Keywords: Languages; Almada negreiros; Aesthetics